Assessment of Hsp90β-selective inhibitor safety and on-target effects - Tyelor S. Reynolds; Sanket J. Mishra; Brian S. J. Blagg (Scientific Reports)
Abstract The heat shock protein 90 (Hsp90) family of molecular chaperones mediates the folding and activation of ~ 400 client proteins, many of which contribute to oncogenesis. As a result, Hsp90 pan-inhibitors, which inhibit all four Hsp90 isoforms, have been investigated in the clinic for the treatment of cancer. Unfortunately, detrimental side effects were observed and hindered the clinical development of pan-Hsp90 inhibitors. The two most common on-target toxicities, cardio-toxicity and ocular-toxicity, have been attributed to inhibition of the Hsp90α isoform. As an alternative strategy, Hsp90β-selective inhibitors have been developed, which have shown promising anti-cancer activity in vitro and in vivo in combination with immune-checkpoint blockade therapy. This study aims to assess the potential risks of cardio-toxicity and ocular-toxicity exhibited by Hsp90β-selective inhibitors in vitro. In summary, the Hsp90β-selective NDNB1182 was found to avoid the cardio- and ocular-toxicity typical of Hsp90 pan-inhibitors (e.g. 17-AAG), providing a promising path toward the generation of isoform-selective Hsp90 inhibitors.